2021
DOI: 10.1002/smi.3043
|View full text |Cite
|
Sign up to set email alerts
|

Coping flexibility: Variability, fit and associations with efficacy, emotion regulation, decentering and responses to stress

Abstract: Coping flexibility is a promising approach to understanding risk and resilience, but it has been conceptualized in various ways. The aim of this study was to test convergence of coping-related flexibility measures with other coping-related competencies (coping self-efficacy, emotion regulation, decentering) and ways of coping.Participants were 885 students (M age = 21.5 years) who completed measures of flexibility (seven subscales), coping self-efficacy, emotion dysregulation, decentering, and ways of coping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Many studies indicate that emotional flexibility is either a predictor or a significant component for the effectiveness, self-awareness, self-confidence and psychological well-being of teachers and professions related to psychological competencies (Bullis et al, 2019 ; MacIntyre et al, 2019 ). This may be related both to the ability to transform the distress and disorders of patients, students and work partners, as well as to cope with one’s own stress (Zimmer-Gembeck, 2021 ). Teaching coping strategies should be closely related to the development of the psychological flexibility of professional psychologists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies indicate that emotional flexibility is either a predictor or a significant component for the effectiveness, self-awareness, self-confidence and psychological well-being of teachers and professions related to psychological competencies (Bullis et al, 2019 ; MacIntyre et al, 2019 ). This may be related both to the ability to transform the distress and disorders of patients, students and work partners, as well as to cope with one’s own stress (Zimmer-Gembeck, 2021 ). Teaching coping strategies should be closely related to the development of the psychological flexibility of professional psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the foregoing, the researchers conclude that emotional flexibility presupposes dynamic and active behavior (Roth et al, 2019 ; Sheppes, 2020 ; Zimmer-Gembeck, 2021 ). Emotionally flexible person is able to adapt to a complex and rapidly changing world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decentering as a metacognitive capacity allows people to reflect on, evaluate and refine their judgment which can be applied to general stress coping (Keser et al, 2020;Zimmer-Gembeck, 2021). Numerous studies indicated the positive association between decentering and positive thinking, a reappraisal of stress, and constructive coping when facing stressful events (Bernstein et al, 2015;Duncan et al, 2021;.…”
Section: Literature Review 1decenteringmentioning
confidence: 99%
“…Люди с выраженной ригидностью копинга склонны к отрицанию стресса или избеганию, к предпочтению способов, которые ранее подтвердили свою эффективность (Екимчик, Крюкова, 2020). В то же время гибкость копинга положительно коррелирует с вовлеченностью и отрицательно -с уходом от стрессовых ситуаций (Zimmer-Gembeck, 2021).…”
Section: успешность копинга и его гибкостьunclassified